Understanding the growth of the bio-struvite production Brevibacterium antiquum in sludge liquors - Simoes, Francisco; Vale, Peter C. J.; Stephenson, Tom; Soares, Ana (Taylor & Francis, 2017)
Biological struvite (bio-struvite) production through biomineralization has been suggested as an alternative to chemically derived struvite production to recover phosphorus from wastewater streams. In this study, statistical experimental design techniques were used to find the optimal growth rate (μ) of Brevibacterium antiquum in sludge liquors. Acetate, oleic acid, NaCl, NH4-N, and Ca2+ were shown to affect the growth rate of B. antiquum. The growth rate reached 3.44 1/d when the bacteria were supplemented with 3.0% w/v NaCl and 1124 mg chemical oxygen demand/L as acetate. However, NaCl was found to hinder the biomineralization of bio-struvite. A two-stage experiment demonstrated that bio-struvite was produced in the presence of acetate. Bio-struvite production was confirmed with X-ray spectroscopy and crystal morphology (prismatic, tabular, and twinned crystal habit) through electron microscope analysis. The bio-struvite production was estimated by measuring phosphate content of the recovered precipitates, reaching 9.6 mg P/L as bio-struvite. Overall, these results demonstrated the optimal conditions required to achieve high growth rates as well as bio-struvite production with B. antiquum. The results obtained in this study could be used to develop a process to grow B. antiquum in wastewater streams in mixed cultures and recover phosphorus-rich products such as struvite.
Keywords: Biomineralization; Centrate; Phosphorus recovery; Wastewater; Mixed-culture